Establishing Spoilage Thresholds of Ground Beef in a Traditional Retail Case Scenario - G. E. Corrette; E. S. Beyer; E. A. Mendez; V. Hay; T. G. O'Quinn; M. D. Chao; J. L. Vipham (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The objective of this study was to determine spoilage in fresh ground beef and the perception of consumers regarding alteration of sensory characteristics, as well as the acceptability at different days of shelf-life. Study Description:Ground beef loaves (n= 84) of 80% lean, 20% fat composition and aerobically packaged were stored in a simulated refrigerated retail case for 6 days. Consumers evaluated visual color, odor, touch, and taste. Instrumental color, lipid oxidation, aerobic plate count, andEnterobacteriaceaecount were determined. The Bottom Line:In this study, color was shown to be the important product characteristic of spoilage to consumers’ satisfaction. Overall, based on this research, ground beef can be displayed for 3 days without being perceived as spoiled by consumers.
Keywords: Ground beef; spoilage; consumers